Effect of Tax Audit and Tax Amnesty on Tax Yield in Southwest, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2021)
The study aimed at investigating the effect of tax audit and tax amnesty on tax yield in southwest Nigeria. Tax audit and tax amnesty are part of the tax administration programmes which serves as government’s instrument for determining and monitoring tax collection. Residents have a natural urge to reduce their tax obligations by intentionally overstating their expenses and producing fraudulent entries and falsehoods in their accounting records. Without a doubt, this shows a lot about Nigeria’s tax administration. The study was carried out in southwest Nigeria which comprises of Ekiti, Ondo, Osun, Oyo, Ogun and Lagos States. Survey research method was used for the study and 302 staff of the audit and risk departments from the State Board of Internal Revenue (SBIR) and Federal Inland Revenue Service (FIRS) formed the population of the study. Taro Yamane sampling technique was adopted to get the sampling size of 172 respondents. The researcher created a closed-ended questionnaire called Tax Administration and Tax Yield (TATY) to gather relevant data for the study. The study found that tax audit has significantly positive link with tax yield while tax amnesty has a negative and substantial correlational influence on tax yield significant relationship with tax yield. It was recommended that tax audits should be undertaken on a regular basis and tax amnesty should be fairly play down because it may reduce future tax revenue.